Communication Behaviour of Women Vegetable Growers of Nainital District of Uttarakhand (Indian Journal of Extension Education, 2017)
Aresearch on communication behaviour of women vegetable growers of Nainital district of Uttarakhand was undertaken to find out information processing behaviour and approaches used by the women vegetable growers. The study was conducted in six villages of Community Development Blocks, Haldwani, Ramnagar and Dhari in Nainital district of Uttarakhand. Data were collected through pre-tested semi- structured interview schedule and Focous Group Discussion from 150 women vegetable growers. The findings of the study revealed that the personal cosmopolite sources, which are part of farming community, live with the farmers, being aware of farmers’ problems, providing new technologies, and having close supervision, can play significant role for bringing agricultural development in the area.